Trapping Activity of Nematode-Trapping Fungus Arthrobotrys dactyloides on the Presence of Sawdust, Microorganisms, and Nematodes - Sudirman, Sudirman; Zawani, Karwati (Jurnal Natur Indonesia, 2011)
Once biological control agents of nematodes are introduced into soil, they must function in a very complex and dynamicenvironment. In soil, both nematodes and their antagonists are influenced by other biotic and abiotic factors. However,our knowledge of the effects of these factors in soil is limited. Hence, instead of focusing on the role of individualorganisms in controlling nematode pests, this research aimed to determine the effects of sawdust, microorganisms,and nematodes on trapping activity of Arthrobotrys dactyloides. Experiments were conducted with “standardslide test” and “soil microcosm” using soil amended with various concentrations or without sawdust, with thepresence or the absence of microorganisms, and with the presence or the absence of nematodes (Caenorhabditiselegans and/or Meloidogyne javanica). The experiments were carried out with completely randomized design anddata were analyzed with analysis of variance followed by Tukey’s Honestly Significant Different test. Resultsshowed that sawdust did not have direct effect on ring formation and trapping activity of A. dactyloides. However,sawdust did have effect on microorganisms and C. elegans which then these two factors stimulated ring formationand trapping activity of A. dactyloides.